Residual β-carotene and cyanide levels in gari produced from unfermented yellow cassava (Manihot esculenta Crantz) using local processing method - Osagie, V.E.; Onimawo, I.A.; Alamu, Emmanuel Oladeji (Sciencedomain International, 2017)
Aims: This study was carried out to determine the level of the retained β-carotene in processing yellow cassava (variety IITA TMS 01/1371 or UMUCASS 38) into gari using local processing method, in addition, it was also carried out to determine the residual cyanide after processing (fermented and unfermented) the yellow-fleshed cassava into gari. Place of Study: Department of Biochemistry, Ambrose Alli University Ekpoma and International Institute for Tropical Agriculture Ibadan. Methodology: High performance liquid Chromatography (HPLC) was used to determine the level of β-carotene in gari produced from fermented and unfermented yellow cassava while the cyanide level was determined by an automated Enzymic method. Results and Discussion: It showed that the gari produced from fermented yellow cassava had a higher level of β-carotene depending on the number of days of fermentation compared with the gari from unfermented yellow cassava. The gari produced from unfermented cassava had the least content of β-carotene (8.076±0.311 ug/g) during the first week of storage compared with those produced from fermented cassava (10.600±0.470 - 20.610±0.098 ug/g). There was a reduction in the β-carotene contents in all groups during the 5week storage period. The rate of loss of β-carotene over a five week period showed that the gari from unfermented cassava had the least rate of loss (0.885 ug/week) compared with the gari from fermented cassava over the same period (0.955-2.447 ug/week). However the level of Hydrogen cyanide (HCN) retained was more in the gari from unfermented yellow cassava (3.160±0.006 mg/100 g) compared with the gari from fermented cassava (0.470±0.046-1.423±0.006 mg/100 g). Conclusion: On the basis of the result, it is suggested that yellow cassava should be fermented before being roasted into gari and adequate method of storage be adopted to reduce loss of β-carotene while in storage.